Early Childhood Teachers' Professional Competence in Mathematics - Dunekacke, Simone; Jegodtka, Aljoscha; Koinzer, Thomas; Eilerts, Katja; Jenßen, Lars (Taylor & Francis, 2021)
This edited volume presents cutting-edge research on the professional competence of early childhood mathematics teachers. It considers professional knowledge, motivational-affective dispositions, skills and performance in early childhood mathematics and outlines future fields of research in this area. The book argues that it is essential for early childhood teachers to prepare a high-quality learning environment and that mathematical competence is highly relevant for children's individual development. Bringing together research from mathematics education, educational science and psychology, it integrates international perspectives and considers the contextual factors that affect the development of children's mathematical competence within Early Childhood Education and Care (ECEC) settings. The book uses a model to describe professional teacher competence that considers the dispositions of early childhood teachers, situation-specific skills of early childhood teachers and the performance of early childhood teachers. The book is the first of its kind to give a comprehensive overview and allows for integrative perspectives and interdisciplinary understanding regarding pre- and in-service ECEC teachers' professional competence in the domain of mathematics. It will be essential reading for academics, researchers and students of early childhood education, mathematics education and teacher education.